Identifikasi Pola Perubahan Tutupan Lahan (Land Cover) Akibat Penggunaan Lahan (Land Use) Menggunakan Algoritma Random Forest Di Kabupaten Bangka Tengah - Ari Ardiansyah; Yudistira Bagus Pratama; Zikri Wahyuzi; Arvi Pramudyantoro; Andesta Granitio Irwan (JOURNAL SAINS STUDENT RESEARCH, 2025)
Central Bangka Regency has been facing growing environmental pressures resulting from the expansion of oil palm plantations, mining operations, and accelerated urban development. These activities have caused considerable changes in land cover, posing a threat to the sustainability of local ecosystems. This study aims to examine land cover dynamics between 2019 and 2022 and to forecast future conditions for 2030 as a basis for sustainable spatial planning. Sentinel-2A satellite imagery was processed using the Google Earth Engine(GEE) platform, employing the Random Forest(RF) algorithm to classify land cover into five categories: forest, water, built-up, oil palm plantations, and barren. Model validation through the Overall Accuracy metric demonstrated strong classification performance, reaching 0.90297 in 2019 and 0.90849 in 2022. The analysis showed a 21.63% reduction in forest area, alongside significant increases in oil palm and built-up land. The projection for 2030 suggests that forest cover may decline to just 3.35% of the total area, with oil palm plantations and built-up land becoming dominant. These results emphasize the necessity of implementing sustainable land-use management strategies to maintain a balance between economic growth and environmental conservation in Central Bangka Regency.